Évaluation du taux de cholestérol et les maladies cardiovasculaires chez les hypertendus. - Kaim, Hamida; Kebaili, Nabila (My University, 2020)
Our epidemiological research has shown a link between exposure to cardiovascular risk factors early in life and cardiovascular events in later life. High blood pressure (HBP) and Hypercholesterolemia are important modifiable risk factors (RF) for cardiovascular disease (CVD), which can be defined as a clinical or biological condition that are major components of risk prediction algorithms. Estimating cardiovascular risk is the first step in the primary prevention of CVD. The main objective is the screening and analysis of the main cardiovascular risk factors in 103 patients, who were randomly selected among the consulting patients, and almost all of whom suffer from high blood pressure. This is a cross-sectional study carried out by administering a questionnaire and taking anthropometric measurements. The estimation of cardiovascular risk was based on a method developed and based on data from the clinical examination and the interview (age, sex, systolic blood pressure) without taking into account biological data. Our population is composed of 103 persons working in private analysis laboratory in the wilaya of Mostaganem. So our research made it possible to highlight the clear interaction between cardiovascular risk and excess cholesterol.In the same way as hypertension but les for smoking or a sedentary lifestyle.
Keywords: High blood pressure (HBP); cardiovascular disease; hypercholesterolemia